Implementasi Aplikasi Pendaftaran Peserta Didik Baru Berbasis Online Pada Smp Negeri 1 Wewewa Tengah - Melia Rika Umbu (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The rapid development of science and technology particularly in the field of Internet technology played a major role in various aspects of life.Internet technology development requires the ability of human resources to master and follow the development of Internet technology.The application for the new trainee registration /ppdb is the acceptance process for new candidates at the sd level, smp, Sma, The colleges that were previously thought about and designed for the new students' admissions were well designed so that the school could save costs and reduce the risk of whether or not to happen so that the new students' admissions were done more efficient. The problem of registration system of new students who are running at high school 1 negeri wewewa tengah at this time is not quick information that parents and candidate students get, and also the disorderly implementation of the reception of new students for new students candidates, Starting with the registration process, Selection process, until the announcement of the student acceptance results.Therefore the author implemented the web depelopment life cycle method (wdlc) in the creation of online based new learner registration application.Results of the research made a ppdb website that has been adapted to a manual acceptance format and all migrated to the online system.